2009
DOI: 10.2528/pier09073108
|View full text |Cite
|
Sign up to set email alerts
|

Temporal 1-Soliton Solution of the Complex Ginzburg-Landau Equation With Power Law Nonlinearity

Abstract: Abstract-This paper obtains the exact 1-soliton solution of the complex Ginzburg-Landau equation with power law nonlinearity that governs the propagation of solitons through nonlinear optical fibers. The technique that is used to carry out the integration of this equation is He's semi-inverse variational principle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Various solitons and breather solutions in the strongly nonlocal nonlinear media have been found [5][6][7][8]. Most of these studies focus on the shapes of optical beams invariant during propagation in linear and nonlinear media [6][7][8][9][10][11][12][13]. However, the study of the evolution of beams with a change in shape during propagation is rarely reported in literature.…”
Section: Introductionmentioning
confidence: 96%
“…Various solitons and breather solutions in the strongly nonlocal nonlinear media have been found [5][6][7][8]. Most of these studies focus on the shapes of optical beams invariant during propagation in linear and nonlinear media [6][7][8][9][10][11][12][13]. However, the study of the evolution of beams with a change in shape during propagation is rarely reported in literature.…”
Section: Introductionmentioning
confidence: 96%
“…The Klein-Gordon equation (KGE) is a relativistic field equation that is most frequently studied for describing the particle dynamics in quantum field theory [1][2][3][4][5][6][7][8][9][10]. There has been a great deal of theoretical work devoted to the study of exact solution of KGE for various potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these techniques are the Inverse Scattering Transform [1], Lie symmetry method [6], He's semi-inverse variational principle [4], exponential function method, G /G method, Adomian decomposition method [24], variational iteration method [25], collective variables approach [21] and many more. In this paper, one such method of integration will be used to carry out the integration of the governing NLSE to obtain the exact 1-soliton solution.…”
mentioning
confidence: 99%